BUKU BERGAMBAR PENGENALAN HURUF HANGUL PADA AKTIVITAS MAHASISWA - RISKA FARHANI FARHANI; heldi heldi (Universitas Negeri Padang, 2021)
Since the phenomenon of Korean pop popularity by teenage fan groups increased, it caused the enthusiasm of cultural texts reading groups. Reading cultural texts made teenagers recognize the Korean language. This design aimed to introduce Hangul letters to the adolescents and students as the readers of cultural texts which was caused by the Korean pop popularity phenomenon. The methodology used in this design was the glass box method. It was a method of rational thinking objectively and systematically in analyzing something logically. It has limitations from irrational (irrational) thoughts and considerations. Furthermore, the data analysis method used was the 5W + 1H technique which was what, where, who, why, when, and how in order to make it easier to facilitate finding a solution to the problems faced. This Hangul introduction picture-book was entitled